Atomic-scale 3D reconstruction of antiphase boundaries in GaP on (001) silicon by STEM. (November 2018) - Belz, Jürgen; Beyer, Andreas; Volz, Kerstin
Highlights: Introduction of a method for atomic characterization of complex interfaces. Simulation data based 3D reconstruction by ADF STEM micrographs. Application for the case of complexly shaped antiphase boundaries of GaP on Si. Successful reconstruction of various antiphase boundaries at a nearly atomic level. Evaluation of accuracy and viability for small and medium scale STEM micrographs. Abstract: In order to overcome the limitations of silicon-based electronics, the integration of optically active III–V compounds is a promising approach. Nonetheless, their integration is far from trivial and control as well as understanding of corresponding growth kinetics, and in particular the occurrence and termination of antiphase defects, is of great relevance. In this work, we focus on the three-dimensional reconstruction of such boundaries in gallium phosphide from single scanning transmission electron microscopy images. In the high angle annular dark-field imaging mode, the appearance of these antiphase boundaries is strongly determined by the chemical composition of each atomic column and reflects the ratio of transmitted anti- to mainphase. Therefore it is possible to translate measured intensities to the depth location of these boundaries by utilizing simulation data. The necessary spatial resolution for these column-by-column mappings is achieved via electron optical aberration correction within the microscope. Hence, the complete 3D orientation of these defects can be measured at atomic resolution and correlated to growth parameters. Finally, we present a method to reconstruct large areas from well sampled images and retrieve information about complex embedded nanoscale structures at the atomic scale.